Dyslipidaemia is associated with an increased risk of rotator cuff disease: a systematic review. Issue 5 (28th August 2017) - MacDonald, Austin E; Ekhtiari, Seper; Khan, Moin; Moro, Jaydeep K; Bedi, Asheesh; Miller, Bruce S
Abstract : Importance: Rotator cuff disease affects more than 50% of the population over 60 years of age. It has been suggested that dyslipidaemia is associated with the development of rotator cuff disease. Objective: The aim of this review was to present the available literature on the relationship between lipid disorders and rotator cuff disease and to report on the implications of lipid disorders on the surgical management and postoperative healing of rotator cuff tears. Evidence review: Medline, Embase and PubMed were searched from inception until 18 January 2017. Studies were screened and data were extracted in duplicate. A methodological assessment was performed for included studies. Findings: Nine studies were found to meet the inclusion criteria. Seven of the included studies identified an association between the prevalence of dyslipidaemia and rotator cuff disease. Patients with dyslipidaemia were also found to have more severe rotator cuff tears. Conclusions and relevance: The results of this study suggest an association between blood lipid levels and rotator cuff pathology. Specifically, patients with dyslipidaemia are potentially at higher risk for shoulder pain, rotator cuff tears and more severe rotator cuff tears. Further research is required to identify the effect of lipid-lowering medications on the natural history of rotator cuff disease and the impact on conservative and surgical treatment of rotator cuff pathology. Level of evidence: LevelsII–IVclinical studies.